2019
DOI: 10.1590/1678-4162-10538
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade do amido e comportamento ingestivo de novilhos confinados sob efeito de doses de complexo enzimático em dietas de alta densidade energética

Abstract: RESUMO O objetivo do presente trabalho foi avaliar a conversão alimentar, a digestibilidade do amido, o comportamento ingestivo e o escore de sobras da dieta e de fezes de novilhos confinados, suplementados com doses do complexo enzimático (0; 2,5; 5,0 e 7,5g animal-1 dia-1) e alimentados com dieta constituída por 85% de grão de milho e 15% de núcleo proteico, vitamínico e mineral, na base seca, isenta de forragem. O delineamento experimental foi o de blocos ao acaso contendo quatro tratamentos e quatro repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As mentioned by Vigne et al. [ 14 ], when using amylase-based enzyme complexes in feedlot steers, there was an improvement in starch digestion. We also observed that the addition of α-amylase improved the digestibility of starch and ether extract, which demonstrates the action of this enzyme in the degradation of these compounds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned by Vigne et al. [ 14 ], when using amylase-based enzyme complexes in feedlot steers, there was an improvement in starch digestion. We also observed that the addition of α-amylase improved the digestibility of starch and ether extract, which demonstrates the action of this enzyme in the degradation of these compounds.…”
Section: Discussionmentioning
confidence: 96%
“…There are studies on the addition of exogenous enzymes in the diet of production animals, but it is considered insufficient when the experimental condition is in enzymatic association in order to evaluate digestibility, rumen environment and their effects on performance [ [13] , [14] ]. We also agree that further studies are needed in order to seek to improve production in confinement, where a detail can reflect on profitability and consequently sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Meschiatti et al [ 2 ] discovered that the addition of exogenous α-amylase has a synergistic effect with essential oils and their blends, leading to enhanced performance and ketone weight in beef cattle when compared to Monensin. The research conducted by Vigne et al [ 74 ] on fattening animals suggests that the inclusion of enzyme complexes in feed can improve the feed conversion rate by 0.17% per gram, reduce stool dry matter content by 0.47% on the first day, and decrease drinking time by 0.0068 h. Marwan et al [ 75 ] investigated the impact of exogenous plasminase on the digestibility and performance of buffalo calves. The inclusion of enzyme preparation significantly enhanced DMI, nutrient digestibility, average daily gain (ADG), final weight, and feed conversion rate in the calves.…”
Section: Biological Feed Strains and Enzyme Preparationsmentioning
confidence: 99%